A transistor resonant voltage inverter with pulse density modulation for induction heating equipment - Herasymenko, P.Yu. (Технічна електродинаміка, 2015)
Using a pulse density modulation (PDM) for regulating and stabilization of a transistor converter’s load current for
induction heating equipment, with the number of pulses during a modulation period divisible to the half-period of an
inverter’s output voltage is considered in this paper. A mathematical model of the resonant voltage inverter under PDM
and analytical equations for maximum and minimum current amplitudes and their difference determining the swing of
the ripple current’s amplitude were obtained. It is made clear that PDM with the number of pulses during a modulation
period which is divisible to the half-period of the inverter output voltage allows, on average, to reduce the swing of the
ripple current’s amplitude and enlarge the regulation range of the load current. Розглянуто використання НЧ імпульсної модуляції для регулювання та стабілізації струму навантаження
транзисторного перетворювача для установок індукційного нагріву, коли кількість імпульсів за період модуляції
є кратною півперіоду вихідної напруги інвертора. Отримано математичну модель резонансного інвертора
напруги при НЧ імпульсній модуляції та аналітичні вирази максимальної та мінімальної амплітуд струму,
а також різниці між ними, яка визначає розмах пульсації амплітуди струму. Встановлено, що використання
НЧ імпульсної модуляції, завдяки якій кількість імпульсів за період модуляції кратна півперіоду вихідної
напруги інвертора, дозволяє в середньому зменшити розмах пульсації амплітуди струму та розширити діапазон
регулювання струму навантаження. Рассмотрено использование НЧ импульсной модуляции для регулирования и стабилизации тока нагрузки транзисторного
преобразователя для установок индукционного нагрева, когда количество импульсов за период модуляции
кратно полупериоду выходного напряжения инвертора. Получено математическую модель резонансного
инвертора напряжения с НЧ импульсной модуляцией и аналитические выражения максимальной и минимальной
амплитуд тока, а также разницы между ними, которая определяет размах пульсации амплитуды тока. Установлено,
что использование НЧ импульсной модуляции, благодаря которой количество импульсов за период модуляции
кратно полупериоду выходного напряжения инвертора, позволяет в среднем уменьшить размах пульсации
амплитуды тока и расширить диапазон регулирования тока нагрузки.